Local and cardiorenal effects of periodontitis in nitric oxide-deficient hypertensive rats - Herrera, Bruno S.; Martins-Porto, Rodrigo; Campi, Paula; Holzhausen, Marinella; Teixeira, Simone A.; Mendes, Gustavo D.; Costa, Soraia K. P.; Gyurko, Robert; Van Dyke, Thomas E.; Spolidório, Luis Carlos [UNESP]; Muscara, Marcelo N. (Pergamon-Elsevier B.V. Ltd, 2011)
Objective: In this study we have assessed the renal and cardiac consequences of ligature-induced periodontitis in both normotensive and nitric oxide (NO)-deficient (L-NAME-treated) hypertensive rats.Materials and methods: Oral L-NAME (or water) treatment was started two weeks prior to induction of periodontitis. Rats were sacrificed 3, 7 or 14 days after ligature placement, and alveolar bone loss was evaluated radiographically. Thiobarbituric reactive species (TBARS; a lipid peroxidation index), protein nitrotyrosine (NT; a marker of protein nitration) and myeloperoxidase activity (MPO; a neutrophil marker) were determined in the heart and kidney.Results: In NO-deficient hypertensive rats, periodontitis-induced alveolar bone loss was significantly diminished. In addition, periodontitis-induced cardiac NT elevation was completely prevented by L-NAME treatment. on the other hand L-NAME treatment enhanced MPO production in both heart and kidneys of rats with periodontitis. No changes due to periodontitis were observed in cardiac or renal TBARS content.Conclusions: In addition to mediating alveolar bone loss, NO contributes to systemic effects of periodontitis in the heart and kidney. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Periodontitis; Nitric oxide; Neutrophils; Nitrotyrosine; Lipid peroxidation; Heart; Kidney